MENSAGEM DOS DIRIGENTES - Friede, Reis; Neto, Messod Azulay; Filho, Luiz Paulo da Silva Araújo; Athié, Ivan (LexCult: revista eletrônica de direito e humanidades; v. 4 n. 3 (2020): Direitos Humanos em Tempos de PandemiaDO - 10.30749/2594-8261.v4n3p12-13, 2020)
MENSAGEM DOS DIRIGENTES